The effect of heat treatment and skimming on precipitate formation in caprine and bovine milks. Issue 1 (February 2015) - Miloradovic, Zorana N; Kljajevic, Nemanja V; Jovanovic, Snezana T; Vucic, Tanja R; Macej, Ognjen D
<x content-type="archive" xml:space="preserve">Abstract</x> Caprine and bovine milks have a similar overall gross composition, but vary considerably in the ratios of their casein components. These differences in colloidal casein micelles could affect directly or indirectly the heat stability of caprine and bovine milks at their natural pH. In the present work, the differences in colloidal stability of caprine and bovine milk have been studied by analysing the effect of heat treatment and skimming on precipitation of proteins. Raw and heated milk samples (70 °C/5 min, 80°C/5 min and 90°C/5 min) were centrifuged at 600, 2000, and 4500 g. The amount of precipitate formed after skimming was measured and the protein composition of both precipitates and supernatants analysed using the SDS-PAGE (sodium dodecyl sulphate polyacrylamide gel electrophoresis) and densitometry. In caprine milk, the heat treatment prior to skimming had a statistically significant effect on protein precipitation. Centrifugal force had a statistically significant effect on amount of precipitate for both milks, but the amount was 2 to 4 times higher for caprine milk. When defatting the milk for electrophoresis, a centrifugal force of 600 g appeared to be the most appropriate, in order to avoid protein loss and a possible error in the interpretation of results. Results of this study could also serve as the basis for further investigations on adjusting the skimming conditions for caprine milk in industrial dairy processing environment.